EKSPLOITASI ALAM DALAM SENI LUKIS - Adi Irawan; Abd Hafiz; Yasrul Sami (Universitas Negeri Padang, 2012)
Abstract This final work aims to visualize the damage nature are caused by exploitation of humans. The natural exploitation causes increasingly critical condition and noteworthy development. Forms of exploitation of the natural image is packaged in a painting titled: 1). Save The Nature, 2). It almost left, 3). Dominion, 4). Subterranean House, 5). Rest, 6). Build From The Left, 7). Pollution-Free Area, 8). Townsfolk Food Pollution, 9). Phenomenon, and 10). Arid. Denuded forests, landscapes, plants and residential buildings are the main objects in the cultivation of this final works. However, in visual form the authors show changes in shape of the actual object into a form that is imagined. Kata Kunci : Eksploitasi alam, Karya Seni Lukis